A Systematic Literature Review on the Relationships between Social Presence, Learning Satisfaction and Persistence in Online Learning - Zhang, Yue; Binti Mohamed, Hasnah; Liu, Dan (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Online learning has gained prominence due to numerous success stories, becoming a vital component and instrument for reforming classrooms in higher vocational education. However, the physical detachment inherent in online self-directed learning has raised concerns about student disengagement and isolation during the learning process. Social presence theory provides a unique perspective, methods, and tools for researching online learning. This paper presents a comprehensive analysis of the existing literature, with a focus on social presence, learning satisfaction, and persistence. The results reveal the intricate impact of social presence on learning satisfaction and persistence in online learning environments. A systematic literature review (SLR) was conducted to uncover research findings from May 2013 to June 2023. The selected articles underwent a thorough assessment, and duplicates were removed. The updated criteria for conducting systematic reviews and meta-analyses were used for the literature review. The research team critically analysed, finalised, and deliberated on the significance of the SLR. Out of the 220 papers initially considered, 28 met the specific criteria for adjustment and inclusion/exclusion.